Ameliorative actions of ginseng flower alcoholic extract, on drug-induced hepatotoxicity: A focus on PI3K/AKT/mTOR signaling modulation and intestinal microbiome homeostasis - Minqi Jin; Yibin Xing; Xin Qi; Cheng-bi Cui (Journal of Functional Foods)
This study focused on examining the effects and mechanism of action of ginseng flower alcohol extract (GFAE) on a drug-induced liver injury (DILI) mice model. Ginseng blossoms were extracted with alcohol and examined for their principal active components using high performance liquid chromatography (HPLC), revealing that GFAE was made up of six ginsenoside active components. By creating a mouse model of DILI and measuring its relevant inflammatory indexes and related proteins, it was revealed that GFAE treats DILI by decreasing inflammatory factors, inhibiting inflammation and hepatocyte apoptosis, suppressing abnormal activation of the Phosphatidylinositol 3-Kinase/Protein Kinase B/Mammalian Rapamycin Target Protein (PI3K/AKT/mTOR) signaling pathway, and increasing beneficial bacteria in the intestinal tract, enhancing intestinal flora diversity, and improving the intestinal environment.